Sequential movement skill in Parkinson's disease: A state-of-the-art. (April 2015) - Ruitenberg, Marit F.L.; Duthoo, Wout; Santens, Patrick; Notebaert, Wim; Abrahamse, Elger L.
Abstract: The present work reviews research on the learning and skilled performance of movement sequences in Parkinson's disease (PD). We focus specifically on the serial reaction time (SRT) task, and start by outlining behavioral studies on PD patients and healthy control participants. The literature is not unequivocal: Whereas the majority of studies indicate impaired sequencing skill in PD, still a considerable set of studies opposes this conclusion. We identify and discuss various determinants of sequence skill in PD that may contribute to the inconclusiveness of the literature. One major determinant is the role of dopaminergic medication. It has been hypothesized that while such medication restores dopamine levels in depleted parts of the brain, it may also overdose brain regions in which dopamine depletion is less pronounced. As sequence learning involves the contribution of both affected and unaffected brain areas, dopaminergic medication may enhance particular (motor-related) processes involved in sequence learning, but hinder other (cognition-related) processes that are still intact in PD. We discuss studies supporting this notion and finish with some recommendations for future research: systematically consider the impact of medication, build on models of sequence learning that include both cognitive and motor components, and include more elaborated motor skill to be able to better dissociate cognitive and motor-based problems and explore their interactions.